Transformasi Rural Sufism ke Spiritualitas Kemanusiaan Kalangan Muslimat NU Kedunggalar, Kabupaten Ngawi, Jawa Timur - Mibtadin Mibtadin (Balai Penelitian dan Pengembangan Agama Semarang, 2020)
Women’s organization within Nahdlatul Ulama (NU), Muslimat NU, sub-branch of Kedunggalar, has a role in strengthening women in all aspects of life. In developing human resources on religious education and strengthening national outlook, Muslimat NU routinely holds Pengajian Ahad Wage (Muslim recitals on Sunday). This study used descriptive qualitative method. Data were collected through observation, in-depth interviews, and documentation; and analyzed through the process of of data reduction, data display and drawing conclusions.The findings of this study suggested that Pengajian Ahad Wage held by Muslimat NU Kedunggalar has various meanings, including rural sufism movement, social ethics of rural people, religious expressions of Islam Nusantara, national character building, and women's empowerment media. As a response of the rise of religious extremism movements, right or left wing extremists, it revitalizes friendly Islam through enhancing rural sufism and strengthening human values by placing religion as a social ethic based on al-ukhuwah diniyah, wathaniyah, and insaniyah on the principle of Aswaja an-Nahdliyah for national unity.